STUDI TENTANG PERISTIWA (EVENTSTUDY): SUATU PANDUAN RISET MANAJEMEN KEUANGAN DI PASAR MODAL - Setyawasih, Riyanti (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2007)
An event (like corporate action) can or cannot have information content If the event has the information content, hence the investor will react to the information. It is said that the information content will bring positive/negative signal Hereinafter the signal will instruct the investor decision whether it will invest, hold, or will not invest In generalizing a phenomenon, especially to measure the impact of an event toward something (usually toward the shareholder wealth/abnormal return), sometimes it can generate a wrong conclusion if we use common method In order to avoid the above problems, we can use the method of event study. This method can assist to catch the impact of an event that happened in capital market having completely quick and instant characteristics.